Evaluating Shelley - Clark, Timothy, 1958-; Hogle, Jerrold E. (Published by Edinburgh University Press for the University of Durham, 1996)
Fourteen scholars discuss the work of Percy Bysshe Shelley from a late twentieth-century perspective. Unlike Shakespeare or Wordsworth, Shelley has never been fully accepted into the established literary canon. Even in his own day his value as a poet and a thinker was hotly debated, leaving a legacy of uncertainty for future generations. Divided into three distinct sections, this book argues that Shelley was both ahead of and in tune with his time and ours. The first section evaluates Shelley within the wider contexts of politics, education, authorship and literary theory; the second through close reading of individual works; while the third addresses editing and editorial practice. Together, these essays expand our knowledge and understanding of this problematic poet and come to a powerful conclusion.
Keywords: Shelley, Percy Bysshe, -- 1792-1822 -- Criticism and interpretation.; Shelley, Percy Bysshe, -- 1792-1822 -- Critique et interprétation.; Shelley, Percy Bysshe, -- 1792-1822; Shelley, P. B., -- 1792-1822.; 18.05 English literature.; POETRY -- European -- English, Irish, Scottish, Welsh.; Criticism, interpretation, etc.